2020
DOI: 10.1192/bjb.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness and acceptability of intramuscular clozapine injection: illustrative case series

Abstract: Aims and method A series of eleven patients prescribed intramuscular clozapine at five UK sites is presented. Using routinely collected clinical data, we describe the use, efficacy and safety of this treatment modality. Results We administered 188 doses of intramuscular clozapine to eight patients. The remaining three patients accepted oral medication. With the exception of minor injection site pain and nodules, side-effects were as expected with oral clozapine, and there were no serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…This suggests that the prescription of intramuscular clozapine may achieve long-term clinical improvement and adherence to oral medication, even in those patients who are initially reluctant to engage with clozapine treatment, and that this is maintained even in a less restrictive setting. Consistent with previous studies, 9,11,13 our data found no evidence that intramuscular clozapine differs markedly from oral clozapine tolerability and adverse effects, with the one reported adverse event related to its formulation being swelling at the injection site. However, the lack of additional side-effects reported may be attributed to its short-term use, often during titration and therefore at low doses, and this study was not powered nor designed to assess safety.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This suggests that the prescription of intramuscular clozapine may achieve long-term clinical improvement and adherence to oral medication, even in those patients who are initially reluctant to engage with clozapine treatment, and that this is maintained even in a less restrictive setting. Consistent with previous studies, 9,11,13 our data found no evidence that intramuscular clozapine differs markedly from oral clozapine tolerability and adverse effects, with the one reported adverse event related to its formulation being swelling at the injection site. However, the lack of additional side-effects reported may be attributed to its short-term use, often during titration and therefore at low doses, and this study was not powered nor designed to assess safety.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with an observational study by Hoge et al, 21 according to which drug refusal developed into voluntary acceptance of treatment by most patients. Although preliminary, our data on discontinuation rates among those who did not require intramuscular administrations is in line with previous findings 9,11 that the mere prescription of intramuscular clozapine can increase adherence to clozapine without the need of intramuscular administration. Post hoc analysis also showed that those patients who accepted oral clozapine when offered the intramuscular had lower discontinuation rates compared with patients who declined oral and were administered intramuscular clozapine.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations